Quantitative Mapping Using a GIS/RUSLE Approach of Water Erosion of Soils and the Resulting Carbon Losses : The Case of the Fatick Region (Senegal) - Daniel Gomis; Dethie Ndiaye; Papa Gora Kane; Waly Ngor Sarr; Alioune Badara Dieye (European Scientific Journal, ESJ, 2026)
Water erosion is a complex phenomenon linked to natural and anthropogenic factors. It causes significant damage in terms of soil loss and organic fertilizers. Thus, in the Fatick region, to better understand this problem, this study aimed to map and quantify soil losses linked to water erosion as well as their effects on their carbon content. In this respect, the empirical universal equations of USLE and RUSLE were used. The environmental factors involved in the erosive process (climate, topography, soil, land use) were integrated as an information layer in a Geographic Information System (GIS). The results obtained showed soil losses ranging from 0 to 236 t/ha/year with an average of 50 t/ha/year. The categorization of the results revealed that the levels of "zero" and "very low" soil loss (i.e. ˂ 5 t/ha/year) were the most significant, as they covered 99% of the total area. The vegetation areas appear more resistant to water erosion. The carbon losses caused by this erosion range from 0 to 0.19 t/ha/year. This study thus highlighted the importance of the RUSLE model in the assessment of water erosion and its impacts. The location of these different levels of soil loss, through mapping, could help to better guide intervention areas for good conservation of these soils.